Examining the differential impact of monetary policy in India: a policy simulation approach - Bhat, Sajad Ahmad; Kamaiah, Bandi; Acharya, Debashis (Universidad ESAN. ESAN Ediciones, 2020)
Purpose: Though an accumulating body of study has analysed monetary policy transmission in India, there are few studies examining the differential impact of monetary policy action. Against this backdrop, this study aims to analyse the differential impact of monetary policy on aggregate demand, aggregate supply and their components along with the general price level in India. Design/methodology/approach: The study develops a structural macroeconometric model, which is primarily aggregate and eclectic in nature. The generalized method of movements is used for estimation of behavioural equations, while a Gauss–Seidel algorithm is used for model simulation purposes. Findings: The paper presents the results of two policy simulations from the estimated model that highlight the differential impact of monetary policy. The first one, hike in the policy rate by 5% and second is a reduction in bank credit to the commercial sector by 10%. The results from the first policy simulation experiment reveal that interest hike has a significant negative impact on aggregate demand, aggregate supply and general price level. However, the maximum impact is borne by investment demand and imports followed by private consumption. While as among the components of aggregate supply maximum impact is born by infrastructure output followed by the manufacturing and services sector with the agriculture sector found to be insensitive in nature. The results from the second policy simulation experiment revealed that pure monetary shocks have a significant negative impact on aggregate demand, aggregate supply and general price level. However, the maximum impact is born by private consumption and imports followed by investment demand. While as among components of aggregate supply maximum impact is borne by infrastructure followed by the manufacturing and services sector with the agriculture sector found to be insensitive in nature. From both policy simulation experiments, the study highlighted the relative importance of the income absorption approach as opposed to the expenditure switching effect. Practical implications: The results obtained in this study provides a strong framework for design the monetary policy framework. The results are in a view of the differential impact of monetary policy action among the components of both aggregate demand and aggregate supply. This reflection of differential impact has immense significance for the macroeconomic stabilization as the central bank will have to weigh the varying repercussion of its actions on different sectors. For instance, the decline in output after monetary tightening might be conceived as mild from an overall perspective, but it can be appreciable for some sectors. This differential influence will have an implication for policy design to care for distributional aspects, which otherwise could be neglected/disregarded. Similarly, the output decline may be as a result of either consumption postponement or a temporary slowdown in investment. However, the one emanating due to investment decline will have lasting growth implications compared to a decline in consumer demand. In addition, the relative strength of expenditure changing or expenditure switching policies of trade balance stabilization may have varying consequences in the aftermath of monetary policy shock. Accordingly information on the relative sensitiveness/insensitiveness of different sectors/ components of aggregate demand towards monetary policy actions furnish valuable insights to monetary authorities in framing appropriate policy. Originality/value: The work carried out in the present paper is motivated by the fact that although a number of studies have examined the monetary transmission mechanism in India, a very few studies examining the differential impact of monetary policy action. However, to the best of the knowledge, there is no such studies, which have examined the differential impact of monetary policy in the structural macroeconometric framework. The paper will enrich the existing literature by providing a detailed account of the differential impact of monetary policy among the components of both aggregate demand and aggregate supply in response to an interest rate hike, as well as a decrease in the money supply.

Propósito: Aunque un conjunto de estudios ha analizado la transmisión de la política monetaria en la India, hay pocos estudios que examinen el impacto diferencial de la acción de política monetaria. En este contexto, este estudio tiene como objetivo analizar el impacto diferencial de la política monetaria sobre la demanda agregada, la oferta agregada y sus componentes junto con el nivel general de precios en la India. Diseño/metodología/enfoque: El estudio desarrolla un modelo macroeconométrico estructural, que es principalmente de naturaleza agregada y ecléctica. El método generalizado de movimientos se utiliza para la estimación de ecuaciones de comportamiento, mientras que se utiliza un algoritmo de Gauss-Seidel para fines de simulación de modelos. Hallazgos: El artículo presenta los resultados de dos simulaciones de políticas a partir del modelo estimado que resaltan el impacto diferencial de la política monetaria. El primero, un aumento del tipo de interés oficial del 5% y el segundo, una reducción del crédito bancario al sector comercial del 10%. Los resultados del primer experimento de simulación de políticas revelan que el aumento de los tipos de interés tiene un impacto negativo significativo en la demanda agregada, la oferta agregada y el nivel general de precios. Sin embargo, el impacto máximo lo soportan la demanda de inversión y las importaciones, seguidas del consumo privado. Mientras que entre los componentes de la oferta agregada, el impacto máximo lo tiene la producción de infraestructura, seguida por el sector manufacturero y de servicios, y se considera que el sector agrícola es de naturaleza insensible. Los resultados del segundo experimento de simulación de políticas revelaron que los shocks monetarios puros tienen un impacto negativo significativo en la demanda agregada, la oferta agregada y el nivel general de precios. Sin embargo, el impacto máximo lo soportan el consumo privado y las importaciones, seguidos de la demanda de inversión. Mientras que, entre los componentes de la oferta agregada, el impacto máximo lo soporta la infraestructura, seguida por el sector manufacturero y de servicios, y se considera que el sector agrícola es de naturaleza insensible. A partir de ambos experimentos de simulación de políticas, el estudio destacó la importancia relativa del enfoque de absorción de ingresos frente al efecto de cambio del gasto. Implicaciones prácticas: Los resultados obtenidos en este estudio proporcionan un marco sólido para diseñar el marco de política monetaria. Los resultados se basan en el impacto diferencial de la acción de política monetaria entre los componentes tanto de la demanda agregada como de la oferta agregada. Este reflejo del impacto diferencial tiene una inmensa importancia para la estabilización macroeconómica, ya que el banco central tendrá que sopesar las diferentes repercusiones de sus acciones en diferentes sectores. Por ejemplo, la caída de la producción después del ajuste monetario podría considerarse leve desde una perspectiva general, pero puede ser apreciable para algunos sectores. Esta influencia diferencial tendrá implicaciones para que el diseño de políticas preste atención a los aspectos distributivos, que de otro modo podrían descuidarse o ignorarse. De manera similar, la caída de la producción puede deberse a un aplazamiento del consumo o a una desaceleración temporal de la inversión. Sin embargo, el que se origine debido a la caída de la inversión tendrá implicaciones duraderas para el crecimiento en comparación con una caída en la demanda de los consumidores. Además, la fuerza relativa de las políticas de estabilización de la balanza comercial que modifican el gasto o las políticas de cambio de gasto pueden tener distintas consecuencias después de un shock de política monetaria. En consecuencia, la información sobre la relativa sensibilidad/insensibilidad de diferentes sectores/componentes de la demanda agregada hacia las acciones de política monetaria proporciona información valiosa a las autoridades monetarias a la hora de formular una política adecuada. Originalidad/valor: El trabajo realizado en el presente artículo está motivado por el hecho de que, si bien varios estudios han examinado el mecanismo de transmisión monetaria en la India, muy pocos estudios examinan el impacto diferencial de la acción de política monetaria. Sin embargo, hasta donde sabemos, no existen estudios de este tipo que hayan examinado el impacto diferencial de la política monetaria en el marco macroeconométrico estructural. El artículo enriquecerá la literatura existente al proporcionar una descripción detallada del impacto diferencial de la política monetaria entre los componentes tanto de la demanda agregada como de la oferta agregada en respuesta a un aumento de las tasas de interés, así como a una disminución de la oferta monetaria.
Keywords: Monetary policy; Structural macro-econometric model; Política monetaria; GMM; Modelo macroeconométrico estructural; Policy simulations; Método generalizado de los momentos; Simulaciones de políticas; India; India; https://purl.org/pe-repo/ocde/ford#5.02.04